More sustainable choices in the workplace: a systematic review of nudge theory applications - De Paolis, Giulia; Tiberio, Lorenza; Caffaro, Federica (Frontiers in Psychology, 2025)
Nudge theory proposes subtle changes to the choice environment to influence behavior without restricting autonomy. This scoping review investigates the application of nudging strategies within workplace settings to promote pro-environmental behaviors among employees. Sixteen peer-reviewed empirical studies were selected using PRISMA guidelines from four major databases. The analysis examines the characteristics of the selected studies, theoretical definitions of nudging, intervention types, and observed effectiveness. Findings show a notable increase in publications from 2020 onward, reflecting growing academic and institutional interest in sustainable organizational practices. Most studies are based in high-income Western countries, particularly within the tertiary sector. A clear heterogeneity emerged in how nudging is defined, with only half of the studies explicitly referencing Thaler and Sunstein’s classical framework. Others relied on broader psychological theories, such as social norms or cognitive biases, often without operational clarity. The nudges identified were classified into five categories: informational, reminders and notifications, financial incentives, non-financial incentives, and positioning and default options. Informational nudges and reminders were most commonly applied due to their low intrusiveness and implementation costs, but positioning and incentive-based strategies showed promising results in certain organizational contexts. Effectiveness was highest when nudges were paired with tangible incentives, required minimal effort, and were socially supported by leadership or peers. Conversely, interventions targeting high-cost behaviors or lacking enabling infrastructure were less successful. A lack of long-term follow-up assessments also limits conclusions about the durability of effects. This review highlights the need for consistent operational definitions, context-sensitive design, and longitudinal research. It emphasizes the importance of integrating behavioral insights into organizational structures and processes to foster environmentally responsible behaviors at work and beyond.